Local Anesthetics Lidocaine and Bupivacaine as Pre-emptive Analgesia in Lumbar Region Degenerative Spinal Surgery Patients with Posterior Approach - Yudistira, Andhika; Budhi Prasetio, Agustinus; Siahaan, Lasa Dhakka; Sugiarto, Muhammad Alwy (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Pain management with pre-emptive analgesia is a pain management strategy to reduce acute post-operative pain. AIM: This research aimed to determine the effectiveness of local anesthetics Lidocaine and Bupivacaine to reduce acute pain after the lumbar spine degenerative surgery using a posterior approach. METHODS: This study was observational research with a prospective cohort and was carried out in 2021 at RSUD Dr. Saiful Anwar Malang with a sample of 12 in each test. The samples obtained were in accordance with the inclusion and exclusion criteria. RESULTS: This assessment used was the Visual Analogue Score (VAS); an instrument for measuring the degree of pain experienced by patients with a value range of 0–10. Bupivacaine group achieved a lower VAS score more than lidocaine and the control group with VAS score 2; however, in another group, mostly was dominated by 3–5 VAS score during fullow-up periode. CONCLUSION: This research showed that pre-emptive analgesia administration using local infiltration of Lidocaine or Bupivacaine before incision in degenerative surgery of the lumbar spine with a posterior approach had a significant effect on the scale of acute post-operative pain. Bupivacaine reduces the post-operative pain scale more effectively than Lidocaine up to 48 h postoperatively.